Civil service law and innovative paradigm of administration in governmental institutions - Laurinavičius, Alfonsas (Business, Management and Economics Engineering, 2011)
The article is prepared according to the same name author’s monographic work. Under economic globalization and economic conditions, there are completely new scientific study subjects – public and private interests as well as their interaction and competition. The article reflects the new social phenomenon: to innovatively develop and reform the twenty-first century Public Administration (statutory) bodies. The author reveals the democratic legitimation of market mechanisms and the interoperability issues, creating preconditions for meaningful implementation of the new public administration and public management. The subject matter is wide and presents a study of a more limited objective – to define the managerial (social) public interest, its implementation measures, and recent trends.